Improving the Thermostability and Activity of Transaminase From Aspergillus terreus by Charge-Charge Interaction - Cao, Jia-Ren; Fan, Fang-Fang; Lv, Chang-Jiang; Wang, Hong-Peng; Li, Ye; Hu, Sheng; Zhao, Wei-Rui; Chen, Hai-Bin; Huang, Jun; Mei, Le-He (Frontiers in Chemistry, 2021)
Transaminases that promote the amination of ketones into amines are an emerging class of biocatalysts for preparing a series of drugs and their intermediates. One of the main limitations of (R)-selective amine transaminase from Aspergillus terreus (At-ATA) is its weak thermostability, with a half-life (t1/2) of only 6.9 min at 40°C. To improve its thermostability, four important residue sites (E133, D224, E253, and E262) located on the surface of At-ATA were identified using the enzyme thermal stability system (ETSS). Subsequently, 13 mutants (E133A, E133H, E133K, E133R, E133Q, D224A, D224H, D224K, D224R, E253A, E253H, E253K, and E262A) were constructed by site-directed mutagenesis according to the principle of turning the residues into opposite charged ones. Among them, three substitutions, E133Q, D224K, and E253A, displayed higher thermal stability than the wild-type enzyme. Molecular dynamics simulations indicated that these three mutations limited the random vibration amplitude in the two α-helix regions of 130–135 and 148–158, thereby increasing the rigidity of the protein. Compared to the wild-type, the best mutant, D224K, showed improved thermostability with a 4.23-fold increase in t1/2 at 40°C, and 6.08°C increase in T5010. Exploring the three-dimensional structure of D224K at the atomic level, three strong hydrogen bonds were added to form a special “claw structure” of the α-helix 8, and the residues located at 151–156 also stabilized the α-helix 9 by interacting with each other alternately.